2005
DOI: 10.1063/1.2151227
|View full text |Cite
|
Sign up to set email alerts
|

Splitting and merging of Görtler vortices

Abstract: The splitting and merging of Görtler vortices are experimentally studied by varying the spacings of vertical wires located 10 mm upstream of a concave surface leading edge of 2.0 m radius of curvature subjected to a free-stream velocity of 3.0 m / s. The splitting and merging as the result of the linear instability of the vortices with respect to spanwise perturbation ͑Eckhaus instability͒, occurred when the wire spacing was set to respectively twice and half of the dominant or most amplified wavelength of Gör… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…One single mushroom structure is seen to emerge from the two low-speed streaks marked by the arrows in figures 17(b) and 17(c). This merging of streaks during the nonlinear stage was also observed in the experiments by Mitsudharmadi, Winoto & Shah (2005). The mushrooms to the left of figure 17(e) have already broken down to smaller scales, whereas the midspan structures are still intact.…”
Section: Boundary-layer Response To Free-stream Turbulencesupporting
confidence: 50%
“…One single mushroom structure is seen to emerge from the two low-speed streaks marked by the arrows in figures 17(b) and 17(c). This merging of streaks during the nonlinear stage was also observed in the experiments by Mitsudharmadi, Winoto & Shah (2005). The mushrooms to the left of figure 17(e) have already broken down to smaller scales, whereas the midspan structures are still intact.…”
Section: Boundary-layer Response To Free-stream Turbulencesupporting
confidence: 50%
“…In the validation test case the parameters used were those of the experiment of 17,18 . They considered a boundary layer on a concave plate withR = 2 m and free-stream velocityŪ ∞ = 3 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters adopted for the simulations were based in the experiment of Winoto and collaborators 17,18 and the Prandtl number adopted was Pr = 0.72. The results showed that the primary instability (Görtler vortices) increases the heat transfer rate to values above the turbulent values in the nonlinear development region.…”
Section: Resultsmentioning
confidence: 99%
“…Splitting and merging of the vortices is thus observed when the imposed disturbances deviate from the most amplified wavelength. 4 In the incompressible flows, this single mode analysis has been proved to be successful in different stages of the disturbance development. The readers may refer to Goulpié et al 5 for the linear analysis, Hall, 6 Lee & Liu, 7 Sabry & Liu, 8 Benmalek & Saric, 9 Cunff & Zebib 10 for the nonlinear development and Hall & Horseman, 11 Li & Malik 1 for the secondary instability.…”
Section: Introductionmentioning
confidence: 97%